(untitled) (Ocean and Coastal Research, 2022)
Sandstone reefs play an important role in sheltering a great diversity of organisms. In the north sector of the state of Espírito Santo, southeastern Brazil, the beaches are characterized by ferruginous sandstone reefs in the intertidal zones. These structures have unconsolidated sediment deposited over the reefs, mainly composed of bioclastic fragments of shells and seaweed, like the rhodolith. Rhodoliths are free-living calcareous algae with three-dimensional structures. By modifying the environment's physical characteristics, they create new microhabitats capable of being inhabited by several organisms, such as meio- and macrobenthonic invertebrates. This study sought to investigate the diversity of benthic fauna (macro- and meiofauna) on different substrates (rhodoliths vs. unconsolidated sediment) in the sandstone reef and investigate whether there are differences in benthic community structure between reef zones on Gramuté Beach in the Costa das Algas Environmental Protection Area in Aracruz, Espírito Santo, Brazil. Uni and multifactor analyses showed significant differences in the composition of the benthic fauna between the substrates (p < 0.05). Meiofauna and macrofauna had higher numbers of taxa and diversity associated with rhodoliths compared to with sediments. A multivariate analysis corroborates the results of the univariate, showing variations between substrates and beach zones. The presence of rhodoliths at Gramuté Beach contributes to the heterogeneity of the ecosystem and increases the richness and diversity of the benthos. The character of the benthic community and its dynamic aspects are discussed herein and are extremely important for conservation actions.